Strategi Pemasaran Penerimaan Peserta Didik Baru Di SMK Muhammadiyah 2 Jatinom Klaten - Kusuma, Muhamad Halim (2016)
This study aims to present research findings related to: 1) planning of marketing strategy in the new students admission, 2) the implementation of new students target, 3) the excellences of marketing strategy in the new students admission were used in recruiting students at Muhammadiyah 2 Vocational High School of Jatinom Klaten. This research is qualitative research with etnography research design. Data was collected by deep interview, observation and documentation. Data analysis technique using flow model, whereas the validity of the data examined by source and method triangulation. Results of this research concluded that: 1) Planning of marketing strategy in the new students admission at Muhammadiyah 2 Vocational High School of Jatinom Klaten begins with organizing meetings and coordinating principals and teachers to determine the new admissions plan. At the meeting, the principal plan of activities, committees and implementation of new students admissions. The meeting involved representatives of the student's head, deputy head of the infrastructure, the deputy head of public relations, the guidance counselor, the heads of the program and some subject teachers. 2) On the implementation of targeting the acquisition of new students, the number of students who received a quota or adjusted to the capacity of the schools classrooms. Determination of target acquisition of new students to the principal coordinating the heads of the program, as well as explore the public perception of the benefits of each program. 3) The excellence of marketing strategy in the new students admission that used the promotion of vocational high school through direct publication by visiting the junior high school/ Islamic junior high school and national exam tryout of 9th grade and also not directly publication use the electronic and print media, namely brochures and radio.